UPAYA DINAS KELAUTAN DAN PERIKANAN DALAM KONSERVASI KELAUTAN DI WILAYAH BINTAN TIMUR - fiona dwi yanti (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2022)
The East Bintan area is a conservation area determined by a Ministerial Decree on the grounds that the ecosystem and habitat of the original biota owned by the East Bintan area must be protected. The role of the Department of Marine Affairs and Fisheries in the preservation of the East Bintan area by making policies in the utilization of natural resource management. for supervision. So that the marine ecosystem is not damaged and can be used for welfare, especially for the surrounding community. The preparation of this scientific article aims to provide information about the efforts of the Department of Marine Affairs and Fisheries in the Conservation of the East Bintan Region. The preparation of this article was carried out in June 2022 using a qualitative method with descriptive analysis based on the results of a literature study using secondary data as information. Water Conservation Area in the Eastern Region of Bintan Island, Riau Islands Province with an area of ​​138,561.42 Ha.